Patterns of Foreign Exchange Intervention under Inflation Targeting - Adler, Gustavo (IMF Working Papers; Working Paper ;, 2020)
The paper documents the use of foreign exchange intervention (FXI) across countries and monetary regimes, with special attention to its use under inflation targeting (IT). We find significant differences between advanced and emerging market economies, with the former group conducting FXI limitedly and broadly symmetrically, while the use of this policy instrument in emerging market countries is pervasive and mostly asymmetric (biased towards purchasing foreign currency, even after taking into account precautionary motives). Within emerging markets, the use of FXI is common both under IT and non-IT regimes. We find no evidence of FXI being used in response to inflation developments, while there is strong evidence that FXI responds to exchange rates, indicating that IT central banks in EMDEs have dual inflation/exchange rate objectives. We also find a higher propensity to overshoot inflation targets in emerging market economies where FXI is more pervasive.